Causal effects of gut microbiome on hypertension: a Mendelian randomization study - He, Gang; Cao, Yu; Wang, Houzhao; Lv, Xiaoying (Frontiers in Microbiology, 2023)
Background Previous observational studies have shown that there is an important relationship between gut microbiota and hypertension, we performed a two-sample Mendelian randomization analysis to examine whether the gut microbiota is causally related to hypertension in order to find a basis for potential diagnostic or intervention approaches for hypertension. Methods We obtained significant single nucleotide polymorphisms related to gut microbiota and hypertension from publicly available genome-wide association studies for a two-sample Mendelian randomization study. A total of 18,340 individual genome-wide genotype data were included from 24 population-based cohorts. The inverse-variance weighted meta-analysis is the main analytical method for evaluating causal relationships, and the Mendelian randomization research results have been validated through a series of sensitivity analyses. Results The inverse-variance weighted analysis results indicated that phylum Verrucomicrobia (OR:0.831, 95%CI: 0.710–0.972; p = 0.021), family BacteroidalesS24.7group (OR:0.672, 95%CI: 0.496–0.911; p = 0.01), family Bifidobacteriaceae (OR:0.709, 95%CI:0.569–0.884, p = 0.002), genus Adlercreutzia (OR: 0.991, 95%CI: 0.982–0.999, p = 0.035), genus Phascolarctacterium (OR:0.819, 95%CI:0.685–0.981; p = 0.03), genus LachnospiraceaeNK4A136group (OR:0.990, 95%CI:0.981–0.999; p = 0.025), and genus Ruminococcus2 (OR:0.988, 95%CI: 0.979–0.997; p = 0.008) had protective causal effects on hypertension. The Family Alcaliginaceae (OR:1.011, 95%CI:1.000–1.021, p = 0.04), Genus Anaerostipes (OR:1.375, 95%CI:1.096–1.653; p = 0.025), Genus Collinsella (OR:1.899, 95%CI:1.361–2.348; p = 0.02), and Genus Lachnospiraceae_UCG_010 (OR:1.536, 95%CI:1.072–2.202; p = 0.019) were associated with a higher risk of HTN. The reverse Mendelian randomization analysis results showed no reverse causal relationship between HTN and these bacterial taxa. Conclusion Our Mendelian randomization analysis results indicate a potential causal relationship between these bacterial taxa and hypertension, providing a new perspective for the treatment and prevention of hypertension.